2011
DOI: 10.1080/19440049.2011.609491
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 5-hydroxymethylfurfural during yeast fermentation

Abstract: 5-Hydroxymethyl furfural (HMF) may occur in malt in high quantities depending on roasting conditions. However, the HMF content of different types of beers is relatively low, indicating its potential for degradation during fermentation. This study investigates the degradation kinetics of HMF in wort during fermentation by Saccharomyces cerevisiae. The results indicated that HMF decreased exponentially as fermentation progressed. The first-order degradation rate of HMF was 0.693 × 10(-2) and 1.397 × 10(-2)min(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Among other food products, it can also be found in honey (0.34–58.8 mg/kg), cookies (1.75–35.21 mg/kg), bread (2.2–22 mg/kg), dried fruit (25–2900 mg/kg), coffee beans (100–2186 mg/kg), instant coffee (91.3–4100 mg/kg), fruit juices (2–22 mg/kg), chocolate (42–99 mg/kg), or breakfast cereals (12–47 mg/kg) [ 50 , 51 ]. In brewing malt its content varies widely and ranges from 100–6300 mg/kg, while in the grain of barley it is 100–1200 mg/kg [ 52 , 53 ]. Compared to other food products, the HMF content in beer is relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other food products, it can also be found in honey (0.34–58.8 mg/kg), cookies (1.75–35.21 mg/kg), bread (2.2–22 mg/kg), dried fruit (25–2900 mg/kg), coffee beans (100–2186 mg/kg), instant coffee (91.3–4100 mg/kg), fruit juices (2–22 mg/kg), chocolate (42–99 mg/kg), or breakfast cereals (12–47 mg/kg) [ 50 , 51 ]. In brewing malt its content varies widely and ranges from 100–6300 mg/kg, while in the grain of barley it is 100–1200 mg/kg [ 52 , 53 ]. Compared to other food products, the HMF content in beer is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…HMF has been shown to be converted by yeast into hydroxymethyl furfuryl alcohol with high efficiency (79–84%). Moreover, it has been shown that the degradation of HMF is carried out by yeast preferentially, faster than ethanol fermentation [ 53 ]. The HMF content in commercial beers in different styles has been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…As such, antibacterial compounds derived from plants have been suggested as alternative options or may be a better choice for dental plaque and oral disease control when compared to commonly used chemicals. In addition, due to its ability of inhibiting the three important metabolism enzymes (alcohol dehydrogenase, aldehyde dehydrogenase and pyruvate dehydrogenase) (Modig et al, 2002), HMF was found to inhibit the fermentation of Saccharomyces cerevisiae and itself was primarily converted into 5-hydroxymethylfurfuryl alcohol (Taherzadeh et al, 2000;Modig et al, 2002;Akıllıoglu et al, 2011). Consistently, glucose consumption as well as ethanol yield dramatically declined in the presence of HMF at concentrations at 1g/L or higher during fermentation of yeast (Wikandari et al, 2010).…”
Section: Anti-microbial Effectsmentioning
confidence: 51%
“…HMF is an intermediate product of a cascade of complex reactions (Fallico, Arena, & Zappala, ; LeBlanc et al, ). It is formed through acid‐catalyzed dehydration of hexoses or Maillard reaction (Yang, Zhang, Li, Huang, & Miao, ) and may further decompose into levulinic acid, formic acid, formaldehyde, 2,5‐furandialdehyde (FDA), 5‐methylfurfural (MF), and furfuryl alcohol (Akillioglu, Mogol, & Gökmen, ; Nikolov & Yaylayan, ; Wunderlin, Pesce, Amé, & Faye, ). The concentration of HMF in the honey depends on the equilibrium between its accumulation and degradation processes and it has been a widely‐recognized quality indicator for measuring freshness and detecting overheating of honey (Karabournioti & Zervalaki, ; White, ).…”
Section: Introductionmentioning
confidence: 99%